Hubungan Postur Kerja dengan Kejadian Nyeri Leher pada Pembatik di Kampung Batik Laweyan Surakarta - Firnadi, Jossefa; Handayani, Selfi; Munawaroh, Siti; Wiyono, Nanang (UI Scholars Hub, 2021)
Neck pain is one of the musculoskeletal complaints that people often complain about. Unergonomic work posture is one of the risk factors that can cause neck pain. Among batik craftsmen, unnatural working posture is done in a long time with repetitive movements. This study aimed to determine the relationship between working posture and the incidence of neck pain in batik craftsmen. This research is an analytic observational study with a cross sectional design. Sampling was done using total sampling. The research subjects were 41 batik craftsmen who met the inclusion and exclusion criteria. The working posture of batik craftsmen was measured by the Rapid Upper Limb Assessment (RULA). Neck pain was measured using Neck Disability Index (NDI) questionnaire. Data were analyzed using Kendall's tau correlation test. The results of the study showed most of batik craftsmen working in high risk posture as appeared on 25 people. For neck pain, most of batik craftsmen was in the mild pain category as appeared on 26 people. Based on the bivariate analysis test using the Kendall's tau correlation test, the results were significant (p=0.014; r=0.358). There is a significant relationship with a weak correlation between working posture and the incidence of neck pain among batik craftsmen in Kampung Batik Laweyan Surakarta